2010
DOI: 10.1089/lap.2009.0367
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-Assisted Laparoscopic Nissen Fundoplication with Gastrostomy Preservation in Neurologically Impaired Children

Abstract: Robotic fundoplication has equivalent safety profiles, hospital stay, and time to alimentation, compared to laparoscopic fundoplication, but is not indicated for routine repair due to higher cost, decreased availability, and longer procedure time. Robotic surgery does offer key advantages over standard laparoscopy by employing internally articulating arms, a stable camera platform, and three dimensional imaging. Children presenting for initial or redo fundoplication after feeding gastrostomy are a subset of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…The included studies did not separate their results regarding those children with or without gastrostomies. It is therefore not possible from these data to evaluate whether a gastrostomy affects the above mentioned parameters, but previous reports claim that it is not a practical obstacle for performing a fundoplication .…”
Section: Discussionmentioning
confidence: 99%
“…The included studies did not separate their results regarding those children with or without gastrostomies. It is therefore not possible from these data to evaluate whether a gastrostomy affects the above mentioned parameters, but previous reports claim that it is not a practical obstacle for performing a fundoplication .…”
Section: Discussionmentioning
confidence: 99%
“…We are unable to affirm this with supportive data; however, Lehnert et al have previously demonstrated that hiatal dissection is able to be undertaken 34% faster ( p < 0.05) with robotic assistance than in conventional laparoscopy. In this context, it is also our impression that the advanced technical features of robotic assistance become more apparent and valued in cases that are more complex, such as those involving previous fundoplication, abnormal anatomy and pre‐existing gastrostomy .…”
Section: Discussionmentioning
confidence: 99%
“…A recent article reported robotic-assisted laparoscopic Nissen fundoplication in neurologically impaired children and found that although robotic-assisted fundoplication is not yet indicated for routine fundoplication it does have benefits in children with previous gastrostomy, adhesion from previous abdominal surgery or failed primary fundoplication. Robotic fundoplication has also successfully been reported by others [77][78] . In 2007, a case report was published on the robotic repair of a bochdalek congenital diaphragmatic hernia in a small neonate 79 .…”
Section: Pediatric General Surgerymentioning
confidence: 86%